Consideration of a Credibility Assessment Framework in Model‐Informed Drug Development: Potential Application to Physiologically‐Based Pharmacokinetic Modeling and Simulation. (10th November 2019) - Kuemmel, Colleen; Yang, Yuching; Zhang, Xinyuan; Florian, Jeffry; Zhu, Hao; Tegenge, Million; Huang, Shiew‐Mei; Wang, Yaning; Morrison, Tina; Zineh, Issam
Abstract : The use of computational models in drug development has grown during the past decade. These model‐informed drug development (MIDD) approaches can inform a variety of drug development and regulatory decisions. When used for regulatory decision making, it is important to establish that the model is credible for its intended use. Currently, there is no consensus on how to establish and assess model credibility, including the selection of appropriate verification and validation activities. In this article, we apply a risk‐informed credibility assessment framework to physiologically‐based pharmacokinetic modeling and simulation and hypothesize this evidentiary framework may also be useful for evaluating other MIDD approaches. We seek to stimulate a scientific discussion around this framework as a potential starting point for uniform assessment of model credibility across MIDD. Ultimately, an overarching framework may help to standardize regulatory evaluation across therapeutic products (i.e., drugs and medical devices).